Monumen Keris Sebagai City Branding dalam Strategi Culture Knowledge di Kota Surakarta - Haris Fajar Nugroho (Texture:Art and Culture Journal, 2023)
The development of Surakarta (Solo–the spirit of Java) city construction has various forms of buildings that have the potential to support the city's identity through tourism and culture. One of them is the Keris monument. The Keris monument as a landmark or city marker strongly reflects the identity values of a city (attachment). This study examines the role and function of the Keris Monument as a landmark in cultural knowledge strategy for visiting tourists. This study is field research using qualitative research methods. The results of this research are not in measurement but in contextual descriptive values and meanings. The research approach is based on descriptive qualitative research methods using a naturalistic paradigm. The main focus of this research is to find out the role and function of the Keris monument as city branding in support of the cultural knowledge strategy in Surakarta. This research was conducted to review developments following the slogan of Surakarta, 'Solo, the Spirit of Java,' which is based on existing ethnic identity as a characteristic of a tourist and cultural city.